DKI Jakarta BAZNAS Strategy in Empowering Disability Groups - Bariyah, Oneng Nurul; Yumna, Laila; Gusniarti, Gusniarti; Handayani, Purwi Lestari; Siregar, Najwa Ulfah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research was conducted at BAZNAS DKI Jakarta on the utilisation of productive zakat for persons with disabilities. The research was motivated by the problems often faced by persons with disabilities as part of the mustadh'afin, who face very problems with their lives and welfare. The research used qualitative research methods. There are two kinds of data sources, namely primary and secondary sources. Primary sources were obtained through interviews and observations. Interviews were conducted with informants, namely BAZNAS managers in charge of empowering disability groups. The author conducted direct interviews with a barista with a hearing impairment who was together with a hearing impaired as a disabled barista. Data analysis uses Miles Huberman's theory, which consists of: data collection, data reduction, data presentation, and conclusion drawing/verification. The results concluded that BAZNAS DKI Jakarta provides special coffee business services for people with disabilities under the name “Café Difabis”. People with disabilities who are fostered are generally hearing-impaired, and there are also people with disabilities. BAZNAS DKI Jakarta conducts partnerships and cooperation with the mayors in DKI Jakarta and the DKI Jakarta Social Service so that in 2024, Café Difabis is located at several points in the city of Jakarta, namely: Front of Blok C Building, Central Jakarta Mayor Office Complex, East Jakarta Mayor Office, South Jakarta Mayor Office, West Jakarta Mayor Office, North Jakarta Mayor Office Complex. The results showed that BAZNAS DKI Jakarta, as a philanthropic institution, has played a role in developing the creative economy of people with hearing disabilities.